The Supreme Court of Ukraine in criminal process: system reform or similar change of the name? - Дригваль, Н. П.; Монастирська , В. Ю. (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2018)
More than six months ago (December 15, 2017) the «newly formed» Supreme Court began its work. In this regard, the article examines the first results of the activities of the Grand Chamber and the Judicial Chamber on Criminal Cases in the Supreme Court. Particular attention is paid to the actual legal positions of the Grand Chamber of the Supreme Court in criminal law and legal proceedings, the validity of the relevant legal positions and their significance for further court practice. The author analyzes the problem points in the activity of the «updated» Supreme Court and makes the proposals for their elimination. The purpose of this article is to analyze the first results and achievements of the activities of the Grand Chamber and Judicial Chamber on Criminal Cases as part of the Supreme Court, the latest court practice in criminal law and legal proceedings, as well as to develop concrete proposals for improving the work of the Supreme Court. Despite the enormous strain on the «renewed» Supreme Court, it must be recognized that the first results of his work leave moderate optimism about the systematic unification of the court practice in criminal law and criminal process. Particular attention deserves the level of structuring and argumentation of court decisions of the Grand Chamber of the Supreme Court, an example of which should serve also cassation courts in the Supreme Court when making their decisions. On the whole, we will hope that the «fervor» with which the judge of the Supreme Court began to work will not be extinguished in the near future and the Supreme Court itself will become a catalyst for qualitative changes in ensuring the rule of law in Ukraine. The main directions of improvement of the Supreme Court’s activity should be: 1) structuring decisions of the Judicial Chamber on Criminal Cases as part of the Supreme Court according to the model of the Grand Chamber of the Supreme Court (with a clear division of the decisions on the points and sub-items, interim and final conclusions, doctrinal and practical analysis of the disputed moments); 2) interpretation at the level of explanations of the evaluative concepts in the updated procedural law (for example, the concepts of «exclusive legal problem», «ensuring the development of law», etc.) need to be substantially filled; 3) it should be more consistent to use the practice of the European Court of Human Rights (with an analysis of not only the legal position of the European Court of Human Rights in a particular case, but also the generalization of the factual circumstances of the case in order to determine the relevance of the case which is the subject of the dispute in proceeding, which is under consideration in the Supreme Court).

Більше ніж півроку тому (15 грудня 2017 року) почав роботу «новостворений» Верховний Суд. З огляду на це в статті досліджуються перші результати діяльності Великої Палати та Касаційного кримінального суду в складі Верховного Суду. Особлива увага звертається на актуальні правові позиції Великої Палати Верховного Суду в кримінальному праві та судочинстві, обґрунтованість відповідних правових позицій та їх значення для подальшої правозастосовної практики. Автори проаналізували проблемні моменти в діяльності «оновленого» Верховного Суду та сформулювали пропозиції щодо їх усунення. Мета статті полягає у тому, щоб проаналізувати перші результати та здобутки діяльності Великої Палати і Касаційного кримінального суду в складі Верховного Суду, останню судову практику в кримінальному праві та судочинстві, а також виробити конкретні пропозиції щодо покращання діяльності Верховного Суду. Незважаючи на величезну завантаженість «оновленого» Верховного Суду, слід визнати, що перші результати його діяльності залишають поміркований оптимізм щодо системної уніфікації практики правозастосування в кримінальному праві та процесі. Особливої уваги заслуговує рівень структурування та аргументації судових рішень Великої Палати Верховного Суду, приклад якої має слугувати і касаційним судам у складі Верховного Суду при винесенні ними рішень. У цілому ж будемо сподіватися, що той «запал», з яким почали працювати судді Верховного Суду, не згасне найближчим часом і саме цей орган стане каталізатором якісних змін у забезпеченні верховенства права в Україні. Основними напрямами вдосконалення діяльності Верховного Суду мають бути: 1) структурування рішень Касаційного кримінального суду Верховного Суду за зразком Великої палати Верховного Суду (з чітким поділом рішення на пункти та підпункти, проміжними й остаточними висновками, доктринальним і практичним аналізом спірних моментів); 2) тлумачення на рівні роз’яснень оцінних понять в оновленому процесуальному законодавстві (наприклад, потребують змістовного наповнення такі поняття, як «виключна правова проблема», «забезпечення розвитку права» тощо); 3) більш послідовним має бути використання практики Європейського суду з прав людини (з аналізом не тільки правової позиції Європейського суду з прав людини в конкретній справі, а й узагальненням фактичних обставин відповідної справи з метою встановлення релевантності тій справі, яка є предметом спору у провадженні, яке перебуває на розгляді в Верховному Суді).
ВЕРХОВНИЙ СУД У КРИМІНАЛЬНОМУ ПРОЦЕСІ: СИСТЕМНА РЕФОРМА ЧИ ПРОСТА ЗМІНА НАЗВИ?
Keywords: Supreme Court; Judicial Chamber on Criminal Cases; court practice; Grand Chamber; legal positions.; Верховний Суд; Касаційний кримінальний суд; судова практика; Велика Палата; правові позиції.